Overexpression of ORMDL3 confers sexual dimorphism in diet-induced non-alcoholic steatohepatitis - Ryan D.R. Brown; Christopher D. Green; Cynthia Weigel; Bin Ni; Francesco S. Celi; Richard L. Proia; Sarah Spiegel (Elsevier, 2024)
Objective: The bioactive sphingolipid metabolites ceramide and sphingosine-1-phosphate (S1P) accumulate with overnutrition and have been implicated in non-alcoholic steatohepatitis (NASH) development. ORMDL3, a negative regulator of the rate-limiting step in ceramide biosynthesis, has been identified as an obesity-related gene. Therefore, we assessed the role of ORMDL3 in diet-induced obesity and development of NASH. Methods: Globally overexpressing Ormdl3-Flag transgenic mice (ORMDL3TG) were fed a western high-fat, carbohydrate and cholesterol enriched diet, with high fructose-glucose drinking water. Physiological, biochemical and sphingolipidomic analyses were employed to measure the effect of ORMDL3 overexpression on NASH development. Results: ORMDL3TG male but not female mice fed a western high-fat diet and sugar water had exacerbated adipocyte hypertrophy together with increased severity of white adipose inflammation and fibrosis. Hepatic steatosis, dyslipidemia, impaired glucose homeostasis, hyperinsulinemia, and insulin resistance were significantly more severe only in obese ORMDL3TG male mice that accompanied dramatic liver fibrosis, inflammation, and formation of hepatic crown-like structures, which are unique features of human and murine NASH. Obesogenic diet induces ORMDL expression in male mice but reduces it in females. Mechanistically, overexpression of Ormdl3 lowered the levels of S1P and ceramides only in obese female mice and antithetically increased them in tissues of obese males. ORMDL3TG male mice exhibited a much greater induction of the UPR, propagating ER stress that contributed to their early development of NASH. Conclusions: This study uncovered a previously unrecognized role for ORMDL3 in sexual dimorphism important for the development and progression of NASH.